Development of cereal bars based on passion fruit peel flour - Souza, Leandro Alves de; Hunaldo, Virlane Kelly Lima; Santos, Leticia Nunes dos; Santos, Leonardo Hunaldo dos; Freitas, Adriana Crispim de; Fontenele, Maria Alves (Brazilian Journal of Production Engineering, 2023)
Brazil produces tons of solid organic waste daily, resulting from the food industry, which compromise the ecosystem, since they are highly polluting materials. A large part of this waste is generated by juice extracting industries, which, when processing fruits, discard husks, albedos, seeds, shavings and vesicles. Passion fruit suffers a lot of loss during processing, as only 30% of the entire weight of the fruit is used, which is the pulp used to extract the juice. In recent years, the search for the use of these residues in the development of products with greater added value, such as flour with a high fiber content, has been the subject of research. The present work had as objective the physical, chemical and microbiological evaluation of the cereal bar formulated with passion fruit peel flour. The cereal bar was subjected to microbiological and physical chemical analysis, showing absence of Staphylococcus aureus, Salmonella and Coliforms. The pH, moisture, water activity, titratable acidity, ash and brix degree were analyzed. At the end of the analysis, it was concluded that the use of passion fruit peel in the production of the cereal bar proved to be viable.